Philippines toward sustainable and rapid growth : recent developments and the agenda ahead - Rodlauer, Markus; International Monetary Fund. (Washington, D.C. International Monetary Fund, 2000)
This Occasional Paper discusses the policies behind the favorable economic performance of the Philippines during the 1990s, when it emerged from a long period of slow growth and economic imbalances and managed to escape the "Asian crisis" relatively unscathed. The Philippines' recent experience suggests valuable lessons for emerging economies' efforts at crisis prevention and management, as well as for the country's own policy choices. This paper describes this experience, focusing on the elements behind the relatively strong performance as well as the remaining reform agenda.
Includes bibliographical references.
Electronic reproduction.
Keywords: Sustainable development -- Philippines; Finance, Public -- Philippines; Monetary policy -- Philippines; Banks and banking -- Philippines; Philippines -- Economic conditions -- 1986-.; Philippines -- Economic policy